Color-tunable and white circularly polarized luminescence through confining guests into chiral MOFs - Fu, Hong-Ru; Zhang, Ruo-Yu; Li, Ting; Wei, Chen-Ying; Liu, Shuang; Xu, Jia-Yi; Zhu, Xueli; Wei, Jiaojiao; Ding, Qing-Rong; Ma, Lu-Fang (Chemical communications (Cambridge, England), 2024)
Herein, chiral metal-organic frameworks (MOFs), DCF-20 and LCF-20, were utilized as matrices for both chirality transfer and energy transfer. HBT1@MOFs and HBT2@MOFs emit excitation-dependent circularly polarized luminescence (CPL) due to excited-state intramolecular proton transfer (ESIPT). HBT1/C152/NIR@MOFs exhibit full-color and white CPL. The luminescence dissymmetry factors ( g lum ) were significantly increased, benefiting from the efficient chirality space transfer and high luminescence efficiency. Chiral metal-organic frameworks DCF-20 and LCF-20 were utilized as matrices for both chirality transfer and energy transfer. The excitation-dependent and full-color circularly polarized luminescence can be obtained.